A Comparative Analysis of Different Turbulence Models for Simulating Complex Turbulent Separated Flows over Cubic Geometries. (October 2019) - Praliyev, Nurgeldy; Sarsen, Aydarkhan; Kaishubayeva, Nazira; Zhao, Yong; Fok, Sai Cheong; Teh, Soo Lee
Abstract: This study is aimed to compare the performance of four Reynolds Averaged Navier Stokes (RANS) turbulence models in simulating complex flow over two- and three-dimensional (2D and 3D) cubic geometries using experimental measurements for model validation. The four turbulence models were k-Epsilon (k-ε), k-Omega (k-ω), Shear Stress Transport (SST) and BSL Reynolds Stress (RSM) models. The model validation was performed by comparative analysis with the experimental values of pressure coefficient around the cubic geometries. It was found that the SST and BSL RSM models performed better than the others in capturing the complex separated flows and strong shear in the boundary layer. The good agreement with empirical data can be attributed to the inclusion of transport effects of turbulence and the anisotropic nature in the formulations of the models.